Increasing Islamic Caring Behavior By Increasing Motivation And Leadership Roles - Muh Abdurrouf; Nursalam Nursalam; Maya Dwi Yustini; Dyah Wiji Puspita Sari; Maulidia Safitri; Mesihatus Safaah (Universitas Muhammadiyah Semarang, 2022)
Islamic Caring is an attitude or action taken based on the values of caring, kindness, and compassion to protect, improve and assist the patient's recovery process based on the Qur'an and Sunnah. Several factors that influence Islamic caring behavior include the role of the leader and the motivation of nurses. The purpose of this study was to determine the relationship between the role of the leader and nurses' motivation with Islamic caring behavior. Methods: This research is quantitative research with a cross-sectional approach. Collecting data using a questionnaire with 118 respondents using the total population technique, statistical test used Spearmen correlation. This research has passed the ethical test with the number 30/KEPK/RSI-SA/XI/2021. Results: The role of the leader in the good category is 88.2%, the motivation of nurses in the high category is 87.3%, and the Islamic caring behavior of nurses in the good category is 93.2%. Conclusion: There is a relationship between the role of the leader and Islamic caring behavior with a strong relationship, as well as the relationship between motivation and Islamic caring behavior with a moderate relationship. Efforts to improve Islamic caring behavior are to increase the motivation of nurses and increase the role of the leader.